2020
DOI: 10.1093/mnras/staa2596
|View full text |Cite
|
Sign up to set email alerts
|

The observational impact of dust trapping in self-gravitating discs

Abstract: We present a 3D semi-analytical model of self-gravitating discs, and include a prescription for dust trapping in the disc spiral arms. Using Monte Carlo radiative transfer, we produce synthetic ALMA (Atacama Large Millimeter/submillimeter Array) observations of these discs. In doing so, we demonstrate that our model is capable of producing observational predictions, and able to model real image data of potentially self-gravitating discs. For a disc to generate spiral structure that would be observable with ALM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
1
12
1
Order By: Relevance
“…particle size. If particles are dominated by their aerodynamic properties (gas-to-particle drag forces only), one might expect only the more well-coupled species to match the gas and decoupled particles to have more axisymmetric structure (Gibbons et al 2012;Cadman et al 2020). Two-dimensional simulations at longer cooling timescales have shown decreasing pitch angle (Shi et al 2016), but we do not observe a considerable decrease in θ with increasing β.…”
Section: Gas and Dust Spiralscontrasting
confidence: 54%
See 2 more Smart Citations
“…particle size. If particles are dominated by their aerodynamic properties (gas-to-particle drag forces only), one might expect only the more well-coupled species to match the gas and decoupled particles to have more axisymmetric structure (Gibbons et al 2012;Cadman et al 2020). Two-dimensional simulations at longer cooling timescales have shown decreasing pitch angle (Shi et al 2016), but we do not observe a considerable decrease in θ with increasing β.…”
Section: Gas and Dust Spiralscontrasting
confidence: 54%
“…Previous work which did not include the gravity from gas to dust (e.g. Gibbons et al 2012;Cadman et al 2020) suggested that large particles form axisymmetric rings in self-gravitating disks, while in our simulations we will show that large particles still form spirals. Thus, there are several differences between our work and Gibbons et al (2012).…”
Section: Particle Drag and Self-gravitysupporting
confidence: 44%
See 1 more Smart Citation
“…However, the origin of the spiral morphology remains unclear. Possibilities that have been investigated include companions, both stellar and planetary, (Dong et al 2015;Fung & Dong 2015;Dong & Fung 2017;Forgan et al 2018b;Price et al 2018b;Huang et al 2018;Dong et al 2018;Veronesi et al 2019;Shen et al 2020) and gravitational instability (GI) , 2005Cossins et al 2009;Dong et al 2015;Hall et al 2016;Meru et al 2017;Forgan et al 2018b;Hall et al 2018;Huang et al 2018;Hall et al 2019Hall et al , 2020Cadman et al 2020b;Chen et al 2021). While it has been demonstrated that GI can be responsible for spiral morphology of some observed discs, it requires the disc-to-star mass ratio, 𝑞, be 0.1 for the spirals to be observable (Cossins et al 2010;Dipierro et al 2014;Dong et al 2015;Hall et al 2016;Kratter & Lodato 2016;Hall et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These spiral arms are believed to induce variability in the mass accretion rate (Lodato & Rice 2005;Vorobyov & Basu 2005, 2015, and they could play important roles in planet formation via dust grain accumulation (Rice et al 2004;Dipierro et al 2015), thermal processing and collisional fragmentation (Boss & Durisen 2005;Boley & Durisen 2008;Ida et al 2008;Booth & Clarke 2016). The morphology of observed spirals may also be used to discriminate self-gravitating disks and to constrain their mass and temperature distributions (Dong et al 2015(Dong et al , 2016(Dong et al , 2018Hall et al 2016;Meru et al 2017;Forgan et al 2018;Cadman et al 2020).…”
Section: Introductionmentioning
confidence: 99%